Vitamin D deficiency in proximal femur fracture patients of South‐East Queensland. (16th March 2020) - Awal, Wasim; Bindra, Randy; Price, Nathan; Sadler, Amanda; Robinson, Ann; Hymer, Isobel; Chen, Joe
Abstract: Objectives: To determine the incidence of hypovitaminosis D in proximal femur fracture (PFF) patients and investigate whether sociodemographic factors or radiographic parameters are associated with vitamin D levels. Methods: This is a consecutive case series of South‐East Queensland patients presenting with low‐energy PFFs. Vitamin D levels and sociodemographic factors (age, sex, postcode, medications and type of residence) were collected from medical records. Radiographic parameters included PFF type and cortical thickness of the femur. Results: A total of 313 patients were included (mean age = 79.5 years), and 105 (34%) were deficient in vitamin D (<50 nmol/L). There was no association between vitamin D levels and sociodemographic factors or radiographic parameters. Eighty‐four (84%) of vitamin D‐deficient patients were not taking vitamin D supplements. Conclusions: Social and demographic factors are not correlated with vitamin D levels in this cohort. Routine vitamin D supplementation may be indicated in ageing patients although it is not always protective of low‐energy fractures.